2007
DOI: 10.1038/sj.bjc.6603637
|View full text |Cite
|
Sign up to set email alerts
|

The late radiotherapy normal tissue injury phenotypes of telangiectasia, fibrosis and atrophy in breast cancer patients have distinct genotype-dependent causes

Abstract: The relationship between late normal tissue radiation injury phenotypes in 167 breast cancer patients treated with radiotherapy and: (i) radiotherapy dose (boost); (ii) an early acute radiation reaction and (iii) genetic background was examined. Patients were genotyped at single nucleotide polymorphisms (SNPs) in eight candidate genes. An early acute reaction to radiation and/or the inheritance of the transforming growth factor-b1 (TGFb1 À509T) SNP contributed to the risk of fibrosis. In contrast, an additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 39 publications
5
70
2
1
Order By: Relevance
“…This large, purpose designed study has been unable to confirm recent reports of significant associations between the TGFB1 (C-509T) SNP and increased risk of radiation fibrosis [20][21][22]. We did not find a significant association between either of the correlated TGFB1 SNPs, L10P (rs1800470) or C-509T (rs1800469), with the development of induration, assessed by the clinician.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This large, purpose designed study has been unable to confirm recent reports of significant associations between the TGFB1 (C-509T) SNP and increased risk of radiation fibrosis [20][21][22]. We did not find a significant association between either of the correlated TGFB1 SNPs, L10P (rs1800470) or C-509T (rs1800469), with the development of induration, assessed by the clinician.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these results were not replicated in a further study by the same group [39]. In a combined analysis of two published studies [20,22] of adjuvant radiotherapy to the breast (a total of 236 patients) it was reported that CT heterozygotes for C-509T had a 3-fold increased risk and TT homozygotes had a 15-fold increased risk of fibrosis following radiotherapy compared with CC homozygotes [22].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chang-Claude et al (2005) reported that the XRCC1 399Gln allele may be protective against the development of acute side-effects after radiotherapy in a study that included a cohort of 446 normal weight Caucasian breast cancer patients who received radiotherapy after breast-conserving surgery. In contrast, Giotopoulos et al (2007) found an association between the 399Gln allele and an increased risk of developing late side effects. Mongani et al (2011) reported that the carriers of the XRCC1-Arg194Trp variant allele in combination with the XRCC1-Arg399Gln wild-type allele had a significant risk of acute radiation-induced skin toxicity.…”
Section: Introductionmentioning
confidence: 87%